Ibu PKK Desa Tana Rara Cerdas Finansial: Aman Memanfaatkan Inovasi Keuangan Digital - Lidia Lali Momo; Antar Maramba Jawa; Emirensiana Dapa Ege; Elfira Umar (LPPM UNIVERSITAS NAHDLATUL WATHAN MATARAM, 2026)
The increasing needs of people in this digital era have encouraged technological innovations to continue developing, changing, and penetrating various aspects of human life. One of the developments that continues to grow today is digital finance. This innovation greatly assists community members, especially MSME actors and other financial managers, such as the PKK women of Tana Rara Village who became the focus of this community service activity. However, in reality, this innovation also creates a dilemma for PKK members who do not yet fully understand the available digital financial services and how to safely utilize these advancements. In response to this situation, the community service team conducted a workshop using a participatory approach. This method was chosen because it was adapted to the contextual conditions of the participants, namely by delivering the material followed by training sessions based on the topics presented. Through this approach, it was found that there was a behavioural change, with 93.3% of participants showing increased awareness of protecting personal data and ensuring password strength according to recommended standards. Likewise, regarding their understanding of digital financial innovations, participants were able to understand and use the features of financial service applications and wisely distinguish official information when applying for online loans. Therefore, it can be concluded that this community service activity had a positive impact on the PKK women of Tana Rara Village, encouraging them to become more aware and knowledgeable about digital and financial literacy